Analysis of The Influence of Increasing Micro, Small and Medium Enterprises (Msmes) Types of Restaurants on Msme Income in Medan City Medan Area District - Luwy Berto Marbun; Uswatun Hasanah; Annisa Ilmi Faried (Journal of Management, Economic, and Accounting, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial and strategic role in increasing the income of MSMEs. Although MSMEs have been recognized for their role in the Medan city economy, they still face challenges and obstacles in their operations. These challenges include limited capital and competition. The purpose of this study was to examine the extent to which capital, profit, labor, and innovation influence the income of MSMEs in restaurants. This study aimed to provide recommendations for empowering MSMEs to support regional economic growth. This study used a sampling technique with the Slovin formula, with 20 samples, and data collection was conducted using a questionnaire distributed to respondents, namely MSME restaurant owners. The data analysis technique used Multiple Linear Regression analysis. The results showed that partially, MSME profit, labor, and business innovation significantly influenced MSME income. Meanwhile, business capital did not significantly influence MSME income. However, simultaneously, these four variables significantly influenced the income of MSMEs in restaurants in Medan City, Medan Area District. Profit, labor, and innovation factors drive revenue growth through operational efficiency and competitiveness, while capital fails to deliver significant impact due to limited access or suboptimal management.